2018
DOI: 10.1080/1747423x.2018.1530312
|View full text |Cite
|
Sign up to set email alerts
|

Peri-urban agricultural land vulnerability due to urban sprawl – a multi-criteria spatially-explicit scenario analysis

Abstract: The loss of agricultural land at urban fringes is often monitored but rarely analysed under different scenarios of urban sprawl. This study adopts a multi-criteria spatially-explicit approach to investigate agricultural land vulnerability to urban sprawl under opposing policy directions in the Adelaide metropolitan area. Six land-use change parameters representing the socioeconomic and land-use planning effects were analysed under the scenarios of; Business-As-Usual (BAU), Accelerated Economic Development (EDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…On the policy side, land use policies [88,89], include a wide range of activities by which governments seek to influence land use and controlling land ownership [11,[45][46][47][48], zoning [16,44,83]. The varying role of local government policies on urban growth [2,10,11,13,15,17,[20][21][22]29,40,41,43,57,61,62,70,71,80,89,99,103,104], is influenced by the state/provincial, national and global context. Developing countries, in particular, are increasingly dominated by government-led policies and measures, and consequently, their urbanization depends on how the government acts, predominantly within these communities.…”
Section: Urban/land Use Policiesmentioning
confidence: 99%
“…On the policy side, land use policies [88,89], include a wide range of activities by which governments seek to influence land use and controlling land ownership [11,[45][46][47][48], zoning [16,44,83]. The varying role of local government policies on urban growth [2,10,11,13,15,17,[20][21][22]29,40,41,43,57,61,62,70,71,80,89,99,103,104], is influenced by the state/provincial, national and global context. Developing countries, in particular, are increasingly dominated by government-led policies and measures, and consequently, their urbanization depends on how the government acts, predominantly within these communities.…”
Section: Urban/land Use Policiesmentioning
confidence: 99%
“…In Buenos Aires, Latin America, a study based on 30 m resolution Landsat images from June 1985 and July 2015 showed that urban land increased from 0.093 ha to 1.835 ha, and 30.28% of new urban land originated from lands under production [20]. Urban sprawl in Australia consumed vast land areas for homes, infrastructure, and commercial buildings; nevertheless, land demand remains important [21]. However, the effect of urbanization on agrarian lands is controlled.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the urbanization pathway of this region showed the evolution process of "LAPS/EAPS→PS→LNPS", which has the characteristic of industrialization driving urbanization development. This is similar to some developing countries, since under the development strategy of high economic growth and environmental protection, it is necessary to sacrifice rural land in the rural-urban fringe [54], such as Vietnam and the Philippines [55]. However, in developed countries, due to strict planning restrictions, land use in the rural-urban fringe changes slowly and is difficult to be used for industrial construction [56].…”
Section: Discussionmentioning
confidence: 77%